The Effect of Financial Performance, Leverage, Credit, and Time on Bad Credit Risk with Company Size as a Moderating Variable - Indah Kumala Dewi (Green Publisher Indonesia, 2024)
The purpose of this study was to determine and analyze the effect of financial performance, leverage, credit, and time on the risk of bad credit with company size as a moderating variable. The research method used in this research is quantitative. The population in this study were 47 commercial banks going public in Indonesia listed on the Indonesia Stock Exchange for the period 2016-2023, so the data used were 141 samples. The results showed that the variables studied had a significant influence on the risk of bad credit. First, the financial performance variable has a coefficient value of 1.84 with a significance value of 0.017. These results indicate that financial performance has a positive effect on the risk of bad debts, with every 1% increase in financial performance will increase non-performing loans by 1.84% ceteris paribus. Second, the leverage variable also has a positive effect on non-performing loans, with a coefficient of 0.17 and a significance value of 0.0055. This indicates that every 1% increase in leverage will increase non-performing loans by 0.17% ceteris paribus. The implication of this study is the importance of tighter risk management in managing financial performance and leverage in commercial banks, especially in volatile periods such as the Covid-19 pandemic. Bank managers should pay attention to these indicators in making strategic decisions to minimize the risk of bad debts. In addition, this study provides insights for regulators to strengthen financial supervision policies to maintain the stability of the banking system in Indonesia.